An unusual new species of Melandrya Fabricius, 1801 (Coleoptera: Melandryidae) with new distributional notes for two additional Melandrya from Southwest China - Yang, Shulin; Liu, Jie (Zootaxa, 2024)
An unusual Melandrya species with raised, pale yellowish-orange elytral spots like many species of Helotidae is described as Melandrya (s. str.) helotoides sp. nov. from Guizhou Province in southwest China. It is the ninth species of Melandrya from China. New distributional records are also provided for Melandrya (Bonzicus) incostata Fairmaire, 1889 and Melandrya (Bonzicus) coccinea (Lewis, 1895). All three species are reported from Leigongshan National Nature Reserve. The record for M. (B.) coccinea represents a new provincial occurrence for Guizhou Province. Habitus illustrations of the three species are provided.